OVERVIEW OF KNOWLEDGE OF EFFECTIVE CONTRACEPTION METHOD ON SELECTED WOMEN IN FERTILE AT NGAWEN VILLAGE DISTRICT MAYUNGAN KLATEN - STIKES DUTAGAMA KLATEN (STIKES DUTAGAMA KLATEN, 2014)
Background: The rate of population growth in Indonesia has reached a high enough rate of 1.3%. Development of population growth should be very worried that one of them prevented by more intensive movement on the implementation of family planning. MKET or effective method of contraception is contraception elected with 95% success (minor failure) if used properly and regularly, which is included in this group is the IUD, implant (implant) MOP and MOW. Coverage acceptor MKET very small compared nonMKET ie, acceptor MKET coverage is 24.36% and 75.64% nonMKET coverage. For it by knowing the level of knowledge about MKET WUS made efforts to improve the coverage of acceptor MKET shopped. Objective: To reveal the knowledge of effective contraceptive methods selected on Women in Rural Mayungan Eligible Ngawen Klaten district. Research Methodology: The study was conducted in the village of Klaten Ngawen Mayungan. This research uses a descriptive research. The subjects in this study were all women of childbearing age who have family in the village of Klaten Ngawen Mayungan. Data collection using the enclosed questionnaire. Data were analyzed by univariate analysis only produces WUS characteristic frequency distribution and univariate analyzes to determine the knowledge about MKET WUS. Results: Respondents who have sufficient knowledge of 65.9% (58 respondents), respondents who have a good knowledge of 28.4% (25 respondents), and respondents who have less knowledge of 5.7% (5 respondents). Conclusion: Most of the overview knowledge of Effective Contraceptive Methods in Women Eligible Selected in the village of Klaten Ngawen Mayungan Kecamatanisenough.